What Type of Person Should I Be? About the Appeal to Virtues in Public Health Interventions - Pietro Refolo; Dario Sacchini; Costanza Raimondi; Giovanna Elisa Calabrò; Antonio Gioacchino Spagnolo (Vaccines, 2023)
In line with how ethics has developed for the last three centuries, public health ethics has been widely dominated by a deontological as well as a utilitarian approach. The latter is a version of consequentialism, which states that maximizing utility is the primary goal of the majority of individuals or group action, while, on the other hand, virtue ethics, or at least the appeal to virtues, has been largely marginalized. The aim of this article is twofold. Firstly, we aim to highlight the political and ethical nature of public health interventions, often interpreted and presented as mere scientific enterprises. Secondly, we try to highlight the need to integrate or at least recognize the value of appeal to virtues in public health measures. The analysis will reference the Italian COVID-19 vaccination program as a case study. Initially, we will explore the political and ethical nature of any public health measure, using the implementation of the COVID-19 vaccination program in Italy as an example. Subsequently, we will illustrate the deontological approach to ethics, the utilitarian one, and the virtues one, focusing on the dynamic of the agent’s perspective. Lastly, we will briefly analyze both the Italian COVID-19 vaccination program and the communication campaign that promoted it.